Experimental Study of Patching Method on the Repair of Partially Decayed Teak (Tectona grandis) Wood Beams. (November 2019) - Shulhan, M A; Yasin, I; Chan, E; Salim, A; Prasetya, T
Abstract: The main idea of this research is to investigate the bending strength improvement of patching repair method on partially decayed wood beam. The patching method was carried out by removing the decayed part of the beam and covering the void left by a small piece of identical wood. Epoxy resin with 30 MDGL glue spread and 1 MPa cold pressing was used to stick the small piece of identical wood into the void. Four-point loading method then applied on Jati ( Tectona grandis ) wood beam specimens that have cross sectional dimension of 60 mm by 80 mm and 1200 mm length. Patching method were applied on two types of beams; the tension and compression side repair of the beam. The experimental result showed that both types of the repair could improve the bending strength of the partially decayed beam. However, the tension side repair was not able to restore the bending strength as the compression side repair beam specimen.